2017
DOI: 10.1212/wnl.0000000000003596
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia treatment

Abstract: Objective: To determine the frequency of medication use in patients with dystonia enrolled in an international biorepository study. Methods:In a cross-sectional analysis, we included 2,026 participants enrolled at 37 sites in the United States, Canada, Europe, and Australia through Project 1 of the Dystonia Coalition, an international biorepository study. The primary aim was to assess the frequency of medication classes recommended for treating patients with dystonia, and the secondary aim was to compare chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…A recent study in a large series of patients with different forms of isolated dystonia reported that only 56.6% of LD patients receive botulinum toxin treatment 4 , implying that nearly a half of LD population remain untreated. Symptoms of DTv are known to respond even less well to botulinum toxin 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in a large series of patients with different forms of isolated dystonia reported that only 56.6% of LD patients receive botulinum toxin treatment 4 , implying that nearly a half of LD population remain untreated. Symptoms of DTv are known to respond even less well to botulinum toxin 38 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, the treatment of focal dystonia with or without tremor is directed to temporary symptom management with botulinum toxin injections into the affected muscles. However, this empirical treatment is beneficial for only a fraction of dystonic patients, showing inconsistent benefits across different forms of dystonia 2 4 . Other pharmacological therapies, particularly the therapeutic options that would modulate the pathophysiology of focal dystonia and dystonic tremor, are not existent.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular and cellular mechanisms underlying BSP and other anatomical distributions of isolated dystonia remain fragmentary. Accordingly, treatments for BSP are entirely symptomatic (Pirio Richardson et al, 2017). Most commonly, BSP patients are treated with injections of botulinum toxin although, in some series, almost 50% report minimal improvement, no improvement or worsening of BSP after injections of botulinum toxins (Fernandez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used in the urinary incontinence treatment [29,30], as well as in the neurological field, in the cervical dystonia treatment [31], stroke [32], and Parkinson's disease [33,34], were observed in the following variables: head anteriorized (96%); flexion dorsal (78%); anterior shoulders (>80%); abducted scapula (67%); and right and left foot valgus (54%, Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used in the urinary incontinence treatment [29,30], as well as in the neurological field, in the cervical dystonia treatment [31], stroke [32], and Parkinson's disease [33,34], since its use may promote changes in the motor potential evoked spinal and supraspinal [10]. Finally, in the cardiopulmonary scope, pieces of evidence have been presented in the cardiovascular system response [35]; and in the chronic obstructive pulmonary disease treatment [36], since it has been observed an improvement in respiratory muscle strength and an increase in thoracic cavity mobility after the technique application [37].…”
Section: Discussionmentioning
confidence: 99%